Behind the wallpaper, the wall is scratched, behind the ideology, the void. Emma Labudová's (Un)Awarded Wallpaper Artist - Střelec, Karel (Bohemica Olomucensia, 2023)
The study reflects on the question of whether Ema Labudová's book Tapetář (The Wallpaper Artist) was rightly awarded the 2019 Book Club Literary Award. The author tries to demonstrate that although the text treats a socially desirable topic (the lives of LGBTQ people), this fact cannot obscure the fundamental weaknesses of Ema Labudová's literary art.
Keywords: Ema Labudová; LGBTQ; contemporary Czech prose; ideology